Analisis Laporan Keuangan untuk Menilai Kinerja Keuangan PT Kimia Farma, Tbk - Arin Ramadhiani Soleha (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2022)
PT Kimia Farma, Tbk is engaged in the health sector. By 2020, PT Kimia Farma has 12 factories, 1,278 pharmacies, 451 health clinics, 75 clinical laboratories, 10 opticians, and 3 beauty clinics throughout Indonesia. The type of this research is quantitative descriptive research. In this study, the data was taken from the official website of PT Kimia Farma, Tbk for the period 2019 to 2021. The financial report of PT Kimia Farma, Tbk are presented rationally, transparently, and easily understood. The financial report analysis tool of PT Kimia Farma, Tbk used financial ratios that can be used as a basis for useful information for internal and external parties of the company. The analysis technique was carried out through the calculation of the object of research and concluded concerning the company's financial performance. The ratios used are the Liquidity Ratio, Solvency Ratio, Activity Ratio, and Profitability Ratio. The results of the calculations above assess that the financial performance of PT Kimia Farma, Tbk is still not in good conditions.Keywords: Financial Analysis, Financial Ratios, Financial Performance